Preparation of Fe3O4/SiO2/TiO2/CeVO4 Nanocomposites: Investigation of Photocatalytic Effects on Organic Pollutants, Bacterial Environments, and New Potential Therapeutic Candidate Against Cancer Cells - Marsooli, Mohammad Amin; Rahimi-Nasrabadi, Mahdi; Fasihi-Ramandi, Mahdi; Adib, Kourosh; Eghbali-Arani, Mohammad; Ahmadi, Farhad; Sohouli, Esmail; Sobhani nasab, Ali; Mirhosseini, Seyed Ali; Gangali, Mohamad Reza; Ehrlich, Hermann; Joseph, Yvonne (Frontiers in Pharmacology, 2020)
The new nanocomposite with various molar ratios along with magnetic properties was fabricated via precipitation (assisted by ultrasonic) procedure. The photocatalytic effects of methylene blue (90 % degradation for optimized sample in 100 min) for finding the optimized sample performed under visible light irradiation. Moreover, the photo-antibacterial impacts of bacteria culture environments were found with an optimized sample that had effective destruction of bacteria in comparison to control group. The cytotoxicity properties of panc1 cells and magnetic behaviors of the obtained nanomaterials were evaluated and its IC50 was about 500 mg/L. As an initial step, the structural, morphological and magnetic characteristics of the fabricated nanocomposites were evaluated by Fourier transform infrared spectroscopy (FT-IR), scanning electron microscopy (SEM), X-ray diffraction (XRD), energy dispersive X-ray (EDX) and MAP, UV–visible diffuse reflectance spectroscopy (DRS), and vibrating sample magnetometry (VSM) approaches. Based on SEM results, the size of nanoparticles in fabricated nanocomposite was nearly 50–70 nm for Fe3O4/SiO2/TiO2 and 80–100 nm for Fe3O4/SiO2/TiO2/CeVO4. XRD results showed that desired nanocomposites were truly synthesized without any impurities.